Uso de biofertilizantes en la producción de hortalizas - Muñoz Arias, Nashley Esperanza (2025)
Vegetables are a basic and necessary food for the world's population. The main objective of this research was to determine the use of biofertilizers in vegetable production. In preparing this document, updated information was collected from scientific articles, websites and virtual libraries, considering it as a non-experimental bibliographical research, through the use of synthesis, analysis, and summary. The conclusions determined that nitrogen fixers, phosphorus solubilizers and phytostimulants are considered the main biofertilizers in vegetable production, which are composed of plant remains and microorganisms such as bacteria and fungi, helping to improve soil fertility and plant growth; biofertilizers used in vegetable production may contain boron (B), molybdenum (Mo), zinc (Zn), iron (Fe), manganese (Mn), copper (Cu), chlorine (Cl) and cobalt (Co), essential for the development of horticultural plantations; Among the benefits offered by biofertilizers are the increase in crop productivity, with improvements that can vary between 8% and 15%; reduction in production costs, which makes them more accessible to farmers; and improved soil fertility and increased biodiversity. Biofertilizers also promote environmental protection, since their use reduces dependence on chemical fertilizers and contributes to specific actions such as nitrogen fixation and nutrient solubilization, which favors plant growth.